Architecture of an efficient dual band 1.8/2.5 GHz rectenna for RF energy harvesting - Jahariah Sampe; Noor Hidayah Mohd Yunus; Jumri Yunas; Alipah Pawi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents a highly efficient rectenna of RF energy harvesting systems operating at 1.8 GHz and 2.5 GHz bands for battery-less sensor application. The antenna is designed by CST-MWS. The Schottky diode used for rectifying circuit is HSMS 286B in which designed by Agilent ADS. The key finding of the paper is that the simulated DC output voltage of the rectenna is 1.35 V for low input power of -25 dBm at a high resistance load of 1M Ω. Correspondingly, the RF-DC conversion efficiency of the rectification process is 59.51% and 45.75% at 1.8 GHz and 2.5 GHz, which are high efficiency and much better compared to literature respectively. The rectenna is capable to produce 1.8 V from an input power of -20 dBm. Thus, the proposed RF energy harvesting system offers a promising solution designed for efficient functionality at a low power level of RF energy in the dual band.